Global Longitudinal Strain of the Systemic Ventricle Is Correlated with Plasma Galectin-3 and Predicts Major Cardiovascular Events in Adult Patients with Congenital Heart Disease - Frogoudaki,A.A.; Pantelakis,I.; Bistola,V.; Kroupis, C.; Birba, D; Ikonomidis, I.; Alexopoulos, D; Filippatos,G.; Parissis, J (Medicina (Kaunas.), 2020)
Backround and Objective: We sought to assess in adult congenital heart disease (ACHD) patients the prognostic value of plasma galectin-3 (Gal-3) levels and systemic ventricular global longitudinal strain (SV GLS) as well as their association with NTproBNP and arrhythmogenesis. Materials and Methods: We studied 58 patients (26 men, mean age 37 +/- 16.8 years) with various congenital heart diseases. Patients underwent echocardiogram, 24 h ambulatory ECG monitoring, while NTproBNP and Gal-3 were measured. They were followed up (median of 790.5 days -IQR 350.3 days) and major cardiovascular events (MACE) were recorded. Results. Mean Gal-3 levels were 17.07 +/- 6.38 ng/m. Plasma Gal-3 was correlated with LogNTproBNP (r = 0.456, p = 0.001).Gal-3 levels associated with supraventricular tachycardia (SVT) (p < 0.001) and ventricular tachycardia (VT) (p < 0.001), but was not associated with MACE (HR 1.018, 95% CI 0.944-1.098, p = 0.641).Mean SVGLS in patients with systemic left ventricle was -15.91% +/- 4.09%, which was significantly lower compared to patients with systemic right ventricle and patients with single ventricle (-11.42% +/- 3.37% and -11.9% +/- 5.06%, respectively, p = 0.021).SV GLS correlated with plasma Gal-3 (r = 0.313, p = 0.027) and logNTproBNP (r = 0.479, p < 0.001). SVGLS correlated with VT arrhythmias (p = 0.004). NTproBNP predicted MACE (AUC 0.750, p = 0.03). SVGLS also predicted MACE (AUC 0.745, p = 0.03. In multivariate analysis, SVGLS and logNTproBNP maintained their predictive value (p = 0.004 and p = 0.009, respectively) Conclusion: In ACHD patients, SV GLS was found to predict MACE independently from NTproBNP and correlated with VT. Gal-3 correlated with NTproBNP and SVGLS as well as SVT and VT, but has not been shown to bear significant prognostic potential
IS - 1648-9144 (Electronic) IS - 1010-660X (Print) IS - 1010-660X (Linking) LA - eng PT - Journal Article RN - 0 (Biomarkers) RN - 0 (Blood Proteins) RN - 0 (Galectins) RN - 0 (LGALS3 protein, human) SB - IM
Keywords: Adult; Aged; analysis; Biomarkers; Blood; Blood Proteins; Cardiovascular Diseases; Complications; Etiology; Female; Galectins; Greece; Heart Defects,Congenital; Humans; Male; Middle Aged; pathology; Predictive Value of Tests